Dengue virus in humans and mosquitoes and their molecular characteristics in northeastern Thailand 2016-2018. - Patcharaporn Nonyong (Public Library of Science (PLoS), 2021)
Dengue is hyperendemic in most Southeast Asian countries including Thailand, where all four dengue virus serotypes (DENV-1 to -4) have circulated over different periods and regions. Despite dengue cases being annually reported in all regions of Thailand, there is limited data on the relationship of epidemic DENV infection between humans and mosquitoes, and about the dynamics of DENV during outbreaks in the northeastern region. The present study was conducted in this region to investigate the molecular epidemiology of DENV and explore the relationships of DENV infection in humans and in mosquitoes during 2016-2018. A total of 292 dengue suspected patients from 11 hospitals and 902 individual mosquitoes (at patient's houses and neighboring houses) were recruited and investigated for DENV serotypes infection using PCR. A total of 103 patients and 149 individual mosquitoes were DENV -positive. Among patients, the predominant DENV serotypes in 2016 and 2018 were DENV-4 (74%) and DENV-3 (53%) respectively, whereas in 2017, DENV-1, -3 and -4 had similar prevalence (38%). Additionally, only 19% of DENV infections in humans and mosquitoes at surrounding houses were serotypically matched, while 81% of infections were serotypically mismatched, suggesting that mosquitoes outside the residence may be an important factor of endemic dengue transmission. Phylogenetic analyses based on envelope gene sequences showed the genotype I of both DENV-1 and DENV-4, and co-circulation of the Cosmopolitan and Asian I genotypes of DENV-2. These strains were closely related to concurrent strains in other parts of Thailand and also similar to strains in previous epidemiological profiles in Thailand and elsewhere in Southeast Asia. These findings highlight genomic data of DENV in this region and suggest that people's movement in urban environments may result in mosquitoes far away from the residential area being key determinants of DENV epidemic dynamics.